2006
DOI: 10.1093/brain/awl175
|View full text |Cite
|
Sign up to set email alerts
|

Ross syndrome: a rare or a misknown disorder of thermoregulation? A skin innervation study on 12 subjects

Abstract: Ross syndrome is described as a rare disorder of sweating associated with areflexia and tonic pupil. Since Ross's first description in 1958, approximately 40 cases have been described. We assessed the involvement of cutaneous innervation in 12 subjects with Ross syndrome using quantitative sensory testing, sweating assessment and immunohistochemical study of anhidrotic and hyperhidrotic skin. This evaluation was repeated over time in 4 out of 12 subjects. In addition, we enrolled four subjects with Holmes-Adie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 28 publications
(59 reference statements)
3
95
0
3
Order By: Relevance
“…The latter were asymptomatic subjects with diabetes. Members of the MN Neuropathy Association (79), at interview and by questionnaire, confirmed a previous diagnosis of neuropathy by a neurologist supplemented by EMG (61), nerve conduction study (61), or skin biopsy (6). All Salvatore Maugeri Foundation neuropathy subjects (16) had abnormal neurologic examination, nerve conduction studies, and skin biopsies.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter were asymptomatic subjects with diabetes. Members of the MN Neuropathy Association (79), at interview and by questionnaire, confirmed a previous diagnosis of neuropathy by a neurologist supplemented by EMG (61), nerve conduction study (61), or skin biopsy (6). All Salvatore Maugeri Foundation neuropathy subjects (16) had abnormal neurologic examination, nerve conduction studies, and skin biopsies.…”
Section: Subjectsmentioning
confidence: 99%
“…4 More recently, reduced MC density, distorted MC structure, focal thinning or loss of myelin, and short myelin internodes coupled with decreased sensitivity to touch have been reported. [5][6][7] Functional studies of touch conveyed by cutaneous mechanoreceptors in glabrous skin found that detection of small raised dots (bumps) on a smooth surface using the finger pad was signaled by MCs. 8,9 Based on these studies, we devised a simple device called the Bumps to quantify tactile sensitivity on the finger pads.…”
mentioning
confidence: 99%
“…Similarly, degeneration of cholinergic fibres that innervate the sweat glands has been identified in the anhidrotic skin areas of patients with Ross syndrome 140 . This change, along with severe heat intolerance owing to the inability to sweat, could be used to distinguish patients with Ross syndrome from those with Holmes-Adie syndrome, who also exhibit sweating abnormalities 141 . The pathological abnormalities in patients with Ross syndrome were found to also involve the noradrenergic fibres that innervate arrector pilorum muscles and vessels, and, to a lesser extent, somatic unmyelinated and myelinated nerve fibres 141 .…”
Section: Stromamentioning
confidence: 99%
“…This change, along with severe heat intolerance owing to the inability to sweat, could be used to distinguish patients with Ross syndrome from those with Holmes-Adie syndrome, who also exhibit sweating abnormalities 141 . The pathological abnormalities in patients with Ross syndrome were found to also involve the noradrenergic fibres that innervate arrector pilorum muscles and vessels, and, to a lesser extent, somatic unmyelinated and myelinated nerve fibres 141 . Skin biopsies have also been used to examine autonomic innervation in multiple system atrophy.…”
Section: Stromamentioning
confidence: 99%
“…This emphasizes that skin biopsy is a tool to diagnose small fiber damage rather than neuropathic pain per se. Indeed, a profound skin denervation can be found also in hereditary sensory and autonomic neuropathy type IV with insensitivity to pain [27] as well as in Ross syndrome characterized by altered sweating but no pain complaints [28].…”
Section: Analysis Of Skin Nerve Fibersmentioning
confidence: 99%